Housing laboratory in port cities of the great north of Chile. Modern architecture in an extreme landscape - Grollmus, Víctor Valenzuela (2024)
In the Great North of Chile, there are four port cities; Arica, Iquique, Tocopilla and Antofagasta. Cities that have in common geographical characteristics that shaped and limited their location, which, together with social and urban conditions, shaped the way of inhabiting the desert. Between 1936 and 1976, the housing complexes built by public, private and mixed institutions contributed to the consolidation and growth of these cities as well as becoming references and distinctive cases, not only of the production of modern Chilean architecture, but also installing a architectural modernity in an extreme landscape. Through the review of disciplinary publications, photographic records and field visits, this ongoing doctoral research seeks to reveal how housing complexes materialized ideas, visions and institutional policies that translate into distinctive architectural and urban dimensions colored by the experience of a modernity determined by an extreme landscape that gives off particularities about the built fact, constituting a heritage asset that must not only be valued but also highlighted as paradigms of Modern Latin American Architecture and references of a housing laboratory in the desert.